2013
DOI: 10.1111/1471-0528.12488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating PETCT in the detection and management of recurrent cervical cancer: systematic reviews of diagnostic accuracy and subjective elicitation

Abstract: Background Positron emission tomography-computed tomography (PET-CT) is recommended to triage women for exenterative surgery and surveillance after treatment for advanced cervical cancer.Objective To evaluate diagnostic accuracy of additional whole body PET-CT compared with CT/magnetic resonance imaging (MRI) alone in women with suspected recurrent/persistent cervical cancer and in asymptomatic women as surveillance.Design Systematic reviews. Subjective elicitation to supplement diagnostic information. Search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 33 publications
0
42
0
4
Order By: Relevance
“…In addition, most studies involved patients with a suspected recurrence rather than asymptomatic populations undergoing surveillance. For example, the study that made the main contribution to the overall estimates of sensitivity and specificity in Meads et al 9 included both symptomatic and asymptomatic patients and did not distinguish between them 19 . Another study found that, in 103 patients who had a complete metabolic response to treatment 20 , 13 asymptomatic recurrences were detected by pet or pet-ct. Those patients demonstrated better cause-specific survival than did patients who experienced symptomatic recurrences (59% vs. 19%, p = 0.09); however, it is not clear whether the recurrences were also detected by other methods, and thus the added value of pet-ct is not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, most studies involved patients with a suspected recurrence rather than asymptomatic populations undergoing surveillance. For example, the study that made the main contribution to the overall estimates of sensitivity and specificity in Meads et al 9 included both symptomatic and asymptomatic patients and did not distinguish between them 19 . Another study found that, in 103 patients who had a complete metabolic response to treatment 20 , 13 asymptomatic recurrences were detected by pet or pet-ct. Those patients demonstrated better cause-specific survival than did patients who experienced symptomatic recurrences (59% vs. 19%, p = 0.09); however, it is not clear whether the recurrences were also detected by other methods, and thus the added value of pet-ct is not known.…”
Section: Discussionmentioning
confidence: 99%
“…No studies met the inclusion criteria, and that systematic review was therefore eliminated from further consideration. Two systematic reviews authored by Meads et al 9,10 covered the role of pet-ct in detecting recurrence after complete response to treatment for cervical cancer. The more up-to-date version, which scored highly on the amstar tool for methodologic quality (Table ii), was retained; the older review was excluded from further consideration.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiation of recurrent disease with fi stula formation due to necrosis may be challenging. Serial follow-up and imaging fi ndings in CT or MRI, such as the presence of a focal enhancing mass or low ADC on DWI and FDG avidity in PET/CT, are typical features of recurrence Meads et al 2014 ).…”
Section: Fistulasmentioning
confidence: 99%
“…Correlation of post-and pretreatment imaging and integration of clinical information including radiation therapy technique, radiation fi eld, dose, and time frame since therapy will allow differentiation of therapy-induced complications from tumor recurrence in the majority of cases (Bluemke et al 1991 ;. Serial follow-up in CT and MRI, advanced MRI using DWI and perfusion studies, and/or PET/CT will assist in problem solving in equivocal cases Meads et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%